2011
DOI: 10.1002/ptr.3375
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis sativa and the Endogenous Cannabinoid System: Therapeutic Potential for Appetite Regulation

Abstract: The herb Cannabis sativa (C. sativa) has been used in China and on the Indian subcontinent for thousands of years as a medicine. However, since it was brought to the UK and then the rest of the western world in the late 19th century, its use has been a source of controversy. Indeed, its psychotropic side effects are well reported but only relatively recently has scientific endeavour begun to find valuable uses for either the whole plant or its individual components. Here, we discuss evidence describing the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 213 publications
(356 reference statements)
1
22
0
Order By: Relevance
“…Second, the effects of THC and CP55940 were evaluated in an assay of acid-induced depression of feeding (Stevenson et al, 2006). Feeding is reliably stimulated by THC and other cannabinoid agonists in the absence of pain (Williams et al, 1998;Miller et al, 2004;Jä rbe and DiPatrizio, 2005;Farrimond et al, 2011), suggesting that cannabinoids might be more effective in blocking acid-induced depression of feeding than acid-induced depression of ICSS. The nonsteroidal antiinflammatory drug (NSAID) and clinically effective analgesic ketoprofen (Flecknell, 2009;Sarzi-Puttini et al, 2010) was tested as a positive control in assays of acid-stimulated and acid-depressed behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the effects of THC and CP55940 were evaluated in an assay of acid-induced depression of feeding (Stevenson et al, 2006). Feeding is reliably stimulated by THC and other cannabinoid agonists in the absence of pain (Williams et al, 1998;Miller et al, 2004;Jä rbe and DiPatrizio, 2005;Farrimond et al, 2011), suggesting that cannabinoids might be more effective in blocking acid-induced depression of feeding than acid-induced depression of ICSS. The nonsteroidal antiinflammatory drug (NSAID) and clinically effective analgesic ketoprofen (Flecknell, 2009;Sarzi-Puttini et al, 2010) was tested as a positive control in assays of acid-stimulated and acid-depressed behavior.…”
Section: Introductionmentioning
confidence: 99%
“…It stimulates the appetite centers of the brain, leading to hyperphagia and favoring fat accumulation in adipose tissue. At the same time, CB1R activation reduces energy expenditures (Simopoulos, 2002, DiPatrizio and Piomelli, 2012, Freitas et al, 2017, Mazier et al, 2015, Engeli, 2008, Bisogno and Maccarrone, 2014, Alvheim et al, 2014, Khan et al, 2014a, Cota et al, 2003a, Cota et al, 2003b, Farrimond et al, 2011. These actions contribute to homeostasis in the context of a hunter-gatherer diet of plants, plant-feeding animals, and fish.…”
Section: Role Of Ecb and Cb1r In Obesity And Metabolic Disordersmentioning
confidence: 99%
“…The central role of CB1R in appetite, energy intake, energy conservation, and diet-induced obesity (Freitas et al, 2017, Mazier et al, 2015, Alvheim et al, 2014, Engeli et al, 2005, Engeli, 2008, Cota et al, 2003a, Cota et al, 2003b, Cardinal et al, 2012, DiPatrizio and Piomelli, 2012, Matias and Di Marzo, 2007, Matias et al, 2008, Pagotto et al, 2006, and the hyperphagia and hypothermia resulting from acute stimulation of CB1R by THC (Farrimond et al, 2011, Borgen et al, 1973, makes CB1R a prime suspect for a causative role in the effects of Cannabis use on BMI.…”
Section: Theoretical Explanation For the Decreased Bmi Of Cannabis Usersmentioning
confidence: 99%
“…However, these failed to demonstrate efficacy, in part due to dose‐limiting psychoactive side effects . In addition to Δ 9 ‐THC, there are now known to be over 100 other phytocannabinoids in C. sativa , the majority of which are non‐psychoactive, some of which have appetite‐modulating effects . We have recently shown that cannabigerol (CBG), a non‐psychoactive phytocannabinoid, increases food intake in healthy rats without eliciting neuromotor side effects .…”
Section: Introductionmentioning
confidence: 99%
“…15,16 In addition to Δ 9 -THC, there are now known to be over 100 other phytocannabinoids in C. sativa, the majority of which are non-psychoactive, some of which have appetite-modulating effects. [17][18][19][20] We have recently shown that cannabigerol (CBG), a non-psychoactive phytocannabinoid, increases food intake in healthy rats without eliciting neuromotor side effects. 21,22 Given that patients undergoing chemotherapy commonly report appetite loss, altered food palatability, and early satiety, [23][24][25][26] CBG may have potential to attenuate these anorectic side effects.…”
Section: Introductionmentioning
confidence: 99%